La formación inicial del máster de profesorado: reflexiones en torno a la implementación de una propuesta didáctica para una educación lectoliteraria: Initial training in the teaching master: reflections around the implementation of a didactic proposal for a reading and literary education - Romero Claudio, Carmen; Jiménez Fernández, Rafael (Investigaciones Sobre Lectura, 2019)
Initial training, Literary competence